Pojęcie miłosierdzia w encyklice Jana Pawła II "Dives in misericordia" = The concept of mercy in the Encyclical "Dives in misericordia" by John Paul II - Rutkowska, Izabela (Zielona Góra: Oficyna Wydawnicza Uniwersytetu Zielonogórskiego)
The subject of the research is the Encyclical "Dives in misericordia" of 1980 by John Paul II. The main objective of the study was to define the meaning of the concept "mercy" through the description of the phrases where this lexeme was used as well as to define what the Christian profile of this concept is based on. In both the quantity and quality analysis, the method of linguistic image of the world was applied as well as the cognitive method of description of sentences as "schemes of events".
Keywords: Jan Paweł II, papież (1929-2005); John Paul II; językoznawstwo; linguistics; miłosierdzie; mercy